2022
DOI: 10.3390/plants11131780
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi Induce Tolerance to Salinity Stress in Taro Plantlets (Colocasia esculenta L. Schott) during Acclimatization

Abstract: Soil salinity is a problem that affects soil fertility and threatens agri-food crop production worldwide. Biotechnology, through plant micropropagation and the use of biofertilizers such as arbuscular mycorrhizal fungi (AMF), is an alternative to increase productivity and induce tolerance to salinity stress in different crops. This study aimed to evaluate the effect of different doses of the fungus Glomus intraradices on the ex vitro development of taro (Colocasia esculenta L. Schott cv. Criolla) plantlets und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Colocasia genus-Colocasia esculenta (L.) Schott, known as taro, is an herbaceous plant belonging to the Aracaceae family. This plant is mainly cultivated in tropical and subtropical regions, and its corms are exported worldwide [73] for food purposes owing to their high starch, polysaccharide, and vitamin content and for medicinal value, including their antioxidant, antimetastatic, and anti-inflammatory properties, which occur as a result of secondary metabolites [74,75]. These nutritional, medicinal, and pharmaceutical properties make the taro corm a valuable plant genetic resource.…”
Section: Aracaceaementioning
confidence: 99%
“…Colocasia genus-Colocasia esculenta (L.) Schott, known as taro, is an herbaceous plant belonging to the Aracaceae family. This plant is mainly cultivated in tropical and subtropical regions, and its corms are exported worldwide [73] for food purposes owing to their high starch, polysaccharide, and vitamin content and for medicinal value, including their antioxidant, antimetastatic, and anti-inflammatory properties, which occur as a result of secondary metabolites [74,75]. These nutritional, medicinal, and pharmaceutical properties make the taro corm a valuable plant genetic resource.…”
Section: Aracaceaementioning
confidence: 99%
“…In taro (Colocasia esculenta L. Schott), Baltazar-Bernal et al [10] reported that the early application of arbuscular mycorrhizal fungi (AMF) to taro plantlets obtained in vitro is an alternative to increase or maintain the productivity of this crop in saline soils.…”
Section: Salt Stress and Tolerance Mechanisms In Plantsmentioning
confidence: 99%